2021
DOI: 10.1111/twec.13097
|View full text |Cite
|
Sign up to set email alerts
|

Rules of origin and consumer‐hurting free trade agreements*

Abstract: Economic integration has boosted worldwide fragmentation and resulted in increased international trade over the last few decades. One of the main vehicles of economic integration is the proliferation of regional trade agreements (RTAs). As of September 2020, there were 306 RTAs in force worldwide. 1 Although trade liberalisation through RTAs seems to reduce trade costs, decrease consumer prices and benefit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Malkawi et al have examined the extent to which ROOs still represents an obstacle to the full implementation of GAFTA [13]. Mukunoki and Hirofumi argue that if the threshold required by ROO is too high, even if all trade within the FTA is duty-free, the impact of the aggregate effect may still be negative [14]. Sytsma found that the relaxing rules of origin can allow for more foreign content in exported products has a substantial effect on preference utilization rates [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Malkawi et al have examined the extent to which ROOs still represents an obstacle to the full implementation of GAFTA [13]. Mukunoki and Hirofumi argue that if the threshold required by ROO is too high, even if all trade within the FTA is duty-free, the impact of the aggregate effect may still be negative [14]. Sytsma found that the relaxing rules of origin can allow for more foreign content in exported products has a substantial effect on preference utilization rates [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e system for measuring the level of trade facilitation is becoming more and more complete, but few studies have incorporated trade facilitation into the GTAP model and often only unilaterally pay attention to the smoothness of infrastructure [18,22,23]. erefore, the positive impact of trade facilitation on economic and trade cooperation cannot be ignored in the study of the China-Mauritian free trade zone.…”
Section: Economic Effects Of Improved Trade Facilitationmentioning
confidence: 99%
“…13 [18] Free trade agreements can harm producers and consumers through price increases and tariff exemptions, respectively.…”
Section: [16]mentioning
confidence: 99%
“…Mukunoki (2017) showed that an FTA with ROO may harm consumers if it changes outside firms' location decisions. Mukunoki and Okoshi (2021) investigated a firm's export price manipulation to comply with the ROO, particularly how an MNE's transfer price manipulation affects the inputs imported from outside the FTA. None of these studies, however, consider transfer price manipulation to meet ROO.…”
Section: Literature Reviewmentioning
confidence: 99%